OneNote Online. - Walsh, Heather; Safari eBooks ([Place of publication not identified] : CompuWorks, 2016)
"OneNote Online, part of the Office 365 suite of apps, is a free-form note-taking application for everything from basic notes to drawings, links, and embedded files. A OneNote notebook contains pages and sections, similar to a multi-subject notebook. All work is autosaved, and therefore there is no need to save in OneNote. Students learn to navigate and create notebooks and will work with adding content such as text, images, web content, tables, embedded objects, and more to OneNote Online notebooks. Additionally, students will learn to share and print OneNote Online notebooks."--Resource description page.
Title from resource description page (Safari, viewed September 12, 2016).
Presenter, Heather Walsh.
Keywords: Microsoft OneNote; Microsoft Office; Business -- Computer programs; Electronic books